Discussing Some Aspects of the School Failure As a “Symptom” of School Violence: the from the individual to the institution - Rosane Gumiero Dias da Silva (Educação: Teoria e Prática, 2011)
Currently there are many complaints from school, especially with regard to school violence. It is apparent that the Brazilian educational system has experienced difficulty in preventing such complaints and their symptoms, such as indiscipline, aggression, stealing, looting of the institution, the difficulty of learning – in short, school failure. Some studies – like Tessaro (2001); Patto (1987); Boarini (1998 a), among others – show that it is still common to focus on the student explanations for these behaviors. The school still tends to assign responsibility for the violent act exclusively to the student and his family. Our interest in this study is to discuss some contributions of the educational approach Institutional Pedagogy, which questions the individual practices in relation to violence in schools through its psychosocial approach and presents an alternative collective effort involving teachers, students, parents and community.